[Translated article] Implementation of Recommendations for the Management of Psoriasis During Preconception, Pregnancy, Postpartum, Breastfeeding, and Perinatal Care - I. Belinchón; S. Armesto; P. de la Cueva; L. Ferrándiz; R. Rivera Díaz; J.M. Carrascosa (Elsevier, 2022)
Objective: To analyze degree of implementation of recommendations on the management of psoriasis during preconception, pregnancy, postpartum, breastfeeding, and perinatal care published by the Psoriasis Working Group of the Spanish Academy of Dermatology and Venereology (AEDV). Methods: We designed a structured online survey consisting of closed questions. A link was emailed to all the members of the Psoriasis Working Group to collect their anonymous responses. We also collected sociodemographic, professional, and practice-related data related to the goals of the study and then compiled descriptive statistics to analyze the survey findings. Results: We received 53 responses for analysis. Overall, 96% of respondents were familiar with the recommendations, but very few of them worked in multidisciplinary maternity care units or had access to specific protocols on the management of psoriasis before, during, and after pregnancy in their departments. Seventy percent of dermatologists regularly ask their patients about pregnancy plans, but only 46% ask both men and women. Women also receive more preconception advice than men (54% vs. 19%). Significant variations were observed in the type of advice given. Ninety percent of the dermatologists interrupt topical treatments during pregnancy, and nearly all suspend conventional systemic drugs with the exception of cyclosporin A. Most biologics are also being discontinued in the third trimester, with the exception of certolizumab pegol. Almost all the respondents indicated that they use topical treatments, phototherapy, and certolizumab pegol in breastfeeding mothers. The main barriers to implementing the working group's recommendations are a lack of time, a lack of support, and a lack of robust data. Conclusions: Although the AEDV psoriasis working group's recommendations are widely known, areas for improvement remain. Resumen: Objetivo: Analizar el grado de implementación de las recomendaciones del Grupo de Psoriasis (GPS) sobre las actuaciones a seguir durante la edad fértil, el embarazo, el posparto, la lactancia y el cuidado perinatal en la psoriasis. Métodos: Se diseñó y envió una encuesta cerrada, estructurada y anónima, en formato electrónico a miembros del GPS a través del correo electrónico. Se recogieron las variables sociodemográficas y profesionales de los participantes, y otras relacionadas con los objetivos propuestos. Se realizó un análisis descriptivo. Resultados: Se analizaron 53 encuestas. El 96% de los participantes conocen las recomendaciones del GPS, pero su nivel de participación en unidades de atención multidisciplinar o la disposición de protocolos específicos en los servicios es muy baja. El 70% pregunta de forma regular sobre el deseo gestacional, aunque solo el 46% lo pregunta a varones y mujeres. Se ofrece consejo preconcepcional más a mujeres que a varones (54 vs. 19%). Gran variabilidad en cuanto a los consejos ofrecidos. El 90% suspende tratamientos tópicos durante el embarazo, y prácticamente el 100% los tratamientos sistémicos salvo la ciclosporina A. En el tercer trimestre se suspenden la mayoría de las terapias biológicas a excepción de certolizumab pegol. Los tratamientos tópicos, fototerapia y certolizumab pegol son usados casi por el 100% de los encuestados en la lactancia. La falta de tiempo, de apoyo de los gestores y de datos robustos son las principales limitaciones a la implementación de las recomendaciones. Conclusiones: A pesar de que son ampliamente conocidas, las recomendaciones del GPS aún quedan áreas de mejora.